Phytoextraction of lead and chromium in a land treating unit of an oil refinery using Vetiveria zizanioides (L.) Nash - Racoma, Lizandro C. (2002)
This study aims to determine the possibility of using Vetiveria zizanioides (L.) Nash in the phytoremediation of soil contaminated with lead and chromium and the effect of ethylenediaminetetraacetic acid (EDTA) in the phytoextraction of these materials. EDTA at a concentration of 1 g/kg soil was applied to the root of Vetiveria zizanioides (L.) Nash two weeks after transplanting. The weight of the root and shoot of the plant as well as the concentrations of chromium and lead in them were measured every month for a period of six months. In the six month period, there was a net increase in the concentration of chromium and lead in both the root and the shoot of the plant. At the 6th month, the mean concentration of Cr in the root and shoot were 21.67 mg/kg +/- 2.27 mg/kg and 6.35 mg/kg +/- 1.89 mg/kg respectively. Total accumulation of chromium and lead in Vetiveria zizanioides (L.) Nash increased in time. The concentration oand total accumulation of chromium and lead in the root and shoot of Vetiveria zizanioides (L.) NAsh were not significantly different between 0 g EDTA/kg soil and 1 g EDTA/kg soil. The chromium and lead concentrations and their total accumulations in the root and shoot of Vetiveria zizanioides (L.) Nash were both significantly higher in the root than in the shoot. The total accumulated Cr in the root plus shoot was 21.99 mg +/- 2.38 mg while 10.61 mg +/- 0.24 mg for Pb per cluster of vetiver. The accumulated metal in the plant was still increasing at the 6th month and has not yet reached maximum levels. This study has shown that even without EDTA applied on soil, Vetiveria zizanioides (L.) Nash can be used for phytoremediation of coil contaminated with Pb and Cr.
Thesis (M.S.Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Soils -- Heavy metals content; Vetiver -- Effect of soil acidity on; Phytoremediation; Ethylenediaminetetraacetic acid